Recent Advances in Employer Branding: Literature Review - Sharma, Ravindra; Rana, Geeta; Jain , Vipul (International Journal of Psychosocial Rehabilitation, 2019)
Employer branding (EB) in today’s scenario emerge as a huge tool in management area last few years. Maximum businesses in current era acknowledge the importance of in employee selection, engagement and retention. To realize that competition, Employer Branding is fast emerging as an extended term human resource strategy to draw in and retain talented manpower. Though many research in last few years conducted but many questions are still need to investigate. This paper presented a many new facts and findings which shows new development requirement that require today picture of EB in IT sector.